2018
DOI: 10.31665/jfb.2018.4164
|View full text |Cite
|
Sign up to set email alerts
|

Role of hydrophobicity in food peptide functionality and bioactivity

Abstract: Peptides are important compounds used in the development of functional biomaterials, functional foods and nutraceuticals. The functional and bioactive properties of peptides are directly linked to their structural features, including molecular size, presence or absence of charges, amino acid sequence, hydrophobicity, and hydrophilicity. The role of peptide structures in their bioactivities and functionalities is still emerging. Some bioactive peptides have undesirable taste, which can influence consumer intere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
53
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 79 publications
(56 citation statements)
references
References 104 publications
1
53
0
2
Order By: Relevance
“…Hydrophobicity plays an important role in determining the properties of proteins and peptides, including bioavailability, bitterness score, solubility, self-assembly, and some bioactivities (Acquah, Di Stefano, & Udenigwe, 2018). In this study, surface and molecular (Cardamone & Puri, 1992).…”
Section: Surface and Molecular Hydrophobicity Of Mealworm Proteinsmentioning
confidence: 96%
“…Hydrophobicity plays an important role in determining the properties of proteins and peptides, including bioavailability, bitterness score, solubility, self-assembly, and some bioactivities (Acquah, Di Stefano, & Udenigwe, 2018). In this study, surface and molecular (Cardamone & Puri, 1992).…”
Section: Surface and Molecular Hydrophobicity Of Mealworm Proteinsmentioning
confidence: 96%
“…Functional properties of peptides, such as antioxidant capacity and antimicrobial activity, may be predicted by their molecular weight, net charge, amino acid sequence, hydrophilicity, and hydrophobicity. Bioavailability and functional properties of peptides from proteins depend on type of enzyme used for proteolysis, degree of hydrolysis, and processing conditions [24]. Enzymatic hydrolysis of soybean milk proteins was performed using papain in a laboratory-scale well-equipped bioreactor (Solida Biotech, München, Germany).…”
Section: Enzymatic Hydrolysis Of Soybean Milk Protein In Bioreactormentioning
confidence: 99%
“…This can be justified by the fact that with the increase of the concentration of papain, more amounts of peptide bonds in soybean milk proteins were hydrolyzed and hydrophobic amino acids were exposed. The hydrophobic amino acids offer better reducing activity towards ferric ions and suppress their pro-oxidant activity than native proteins [24,25,62]. In Figure 6, antioxidant capacities of enzyme-treated soybean milks, prepared at different hydrolysis temperatures, are represented.…”
Section: Antioxidant Capacitymentioning
confidence: 99%
“…These amino acid residues can act synergistically to display relevant bioactivities. Hydrophobicity is known to influence peptide self-assembly, taste-active properties, biostability, antioxidant activity and bioavailability [10]. On the other hand, aspartic acid and glutamic acid feature chelate properties, thereby conferring antioxidant effects [9,10].…”
Section: Profile Of Total and Free Amino Acidsmentioning
confidence: 99%
“…The ability of peptides to act as antioxidants depends on the amino acid composition and sequence, and a previous hydrolysis from the native protein is required to gain such bioactivity [9]. Sarmadi et al [9] and Acquah et al [10] reported the influence of amino acids with hydrophobic and/or acid character in the mechanism of the antioxidant action of peptides, as they have the ability to chelate metals and donate electrons to neutralize free radicals. Another factor of great importance for the antioxidant capacity is related to the molecular weight of the peptide chain.…”
Section: Introductionmentioning
confidence: 99%